تيمة المنفى والأوطان المتخيلة -قراءة في خطاب عبد الله إبراهيم النقدي - حويشي, هاجر (جامعة الوادي - University of Eloued, 2022)
تسعى هذه الدراسة إلى الاقتراب من المدوّنة السيرية "خارج المكان" لإدوارد سعيد، في ضوء التحليل الثقافي الذي ارتضاه الناقد العراقي عبد الله إبراهيم، في كتابه "السرد، والهوية، والاعتراف"، حيث عالج إشكالية الكاتب المنفي الّذي يجد نفسه مقتلعا من أرضه، وواقفا على تخوم ثقافات أخرى، فيعيش في غربته حالة اشتياق دائمة لتلك الأرض الّتي غادرها، وطالما أنّه لا يستطيع العودة إليها، فإنّه سيخلق وطنا بديلا، لكنّه في النهاية ليس سوى وطنا متخيّلا، لا يوجد إلا في ذهنه. Abstract This study seeks to approach the biographical code out of place" by Edward Said, in the light of the cultural analysis that the Iraqi critic Abdullah Ibrahim accepted, in his book "Narrative, Identity, and Confession", where he addressed the problem of the exiled writer who finds himself uprooted from his land, standing On the borders of other cultures, he lives in his estrangement in a state of permanent longing for that land that he has returned to, and as long as he cannot return to it, he will fly with a torrent, but in the end it is nothing but an imaginary homeland, which only exists in his mind Keywords: biography, exile, displaced homeland.
مقال
Keywords: السيرة الذاتية، المنفي، الوطن المتخيّل